ИСПОЛЬЗОВАНИЕ МОРФОМЕТРИЧЕСКОГО АНАЛИЗА В ИЗУЧЕНИИ МЕЖВИДОВЫХ ОТНОШЕНИЙ ЛЕГОЧНЫХ ГЕЛЬМИНТОВ ОСТРОМОРДОЙ ЛЯГУШКИ В ПАВЛОДАРСКОЙ ОБЛАСТИ (Experimental biology, 2009)
Synergism and antagonism between two lung helminthes species in the acute-rug frog (Rana arvalis) weredisplayed dependently on the composition with the parasites of the intestine. Mutual negative influence between trematodes with different location was recorded.
Keywords: lung helminthes; acute-rug frog